Analysis of Absolute Stability of Non – Linear Systems Using Lyapunov Method - et. al, B.Sruthi (International Journal of Advanced Science and Technology, 2020)
In this paper we are analyzing the stability of non-linear systems by Lyapunov stability functions. This paper focus on the two methods of Lyapunov stability: Lyapunov indirect method and Lyapunov direct method. concerning the stability of solutions near to a point of equilibrium is the most important type. The idea of system linearization around a given point is used for Lyapunov indirect method and local stability with small stability regions can be achieved. On the other hand the Lyapunov direct method is used for the design and analysis of nonlinear systems. Together , the indirect method and direct method constitute the so- called Lyapunov stability theorem.